N-Butyl-2-Cyanoacrylate Adhesive Versus Absorbable Tacks in Laparoscopic Groin Hernia Repair: A Multicenter Randomized Clinical Trial - Clayton C. Petro, MD; Benjamin K. Poulose, MD; Michael J. Rosen, MD; Alfredo M. Carbonell, II, DO; Adel G. El-Ghazzawy, MD; Jeremy A. Warren, MD; Emanuele Lo Menzo, MD; Ajita S. Prabhu, MD; David M. Krpata, MD; Samuel Szomstein, MD; Vimal Narula, MD; Crystal F. Totten, MD; et al. (Annals of Surgery Open)
Objective:. We aimed to determine whether n-butyl-2-cyanoacrylate (NB2C) adhesive is a safe and effective mechanism for nonpenetrating mesh and peritoneal fixation during laparoscopic groin hernia repair. Background:. Chronic pain after laparoscopic groin hernia repair has been associated with penetrating fixation, but there had been no US Food and Drug Administration–approved devices for nonpenetrating fixation in this context. Methods:. Patients undergoing laparoscopic transabdominal preperitoneal (TAP) or totally extraperitoneal (TEP) groin hernia repair with mesh at 1 of 5 academic medical centers were randomized to mesh (TAP/TEP) and peritoneal (TAP) fixation with NB2C adhesive or absorbable tacks. The primary outcome was improvement in pain (visual analog scale [VAS]) at 6 months. The noninferiority margin was 0.9 (α = 0.025; β = 80%). Recurrence, successful use of the device, quality of life, and rates of adverse events (AEs) were secondary outcomes. Results:. From 2019 to 2021, 284 patients were randomized to either NB2C adhesive or absorbable tacks (n = 142/142). Patient and hernia characteristics were comparable, and 65% were repaired using a TAP approach. The difference in VAS improvement at 6 months with NB2C adhesive was not inferior to absorbable tacks in intention-to-treat and per-protocol analyses, respectively (0.25 [95% CI, −0.33 to 0.82]; P = 0.013; 0.22 [95% CI, −0.36 to 0.80], noninferiority P = 0.011). There were no differences in secondary outcomes including recurrence, successful use of each device to fixate the mesh and peritoneum, quality of life, and additional VAS pain scores. Rates of adverse and serious AEs were also comparable. Conclusions:. NB2C adhesive is safe and effective for mesh fixation and peritoneal closure during laparoscopic groin hernia repair.